Pengaruh Motivasi, Diskusi dalam Reviu Audit, Kompleksitas Tugas, dan Tekanan Waktu terhadap Kinerja Auditor (Studi Pada Inspektorat Kabupaten/Kota Di Provinsi Aceh) - Hujjatun Munawarah; Yossi Diantimala (Program Magister Akuntansi Unsyiah, 2016)
This study aims to determine the effect of the motivation, discussion of audit review, task complexity, and time pressure to the performance of auditors. This research was conducted in Inspektorat Kabuoaten/Kota in the province of Aceh. The sample selected using purposive sampling were 75 auditors. Data obtained by distributing questionnaires to auditors and analysis techniques used were multiple linear regression. The research results showed that motivation and discussion of audit review significant possitive effect the performance of auditor in Inspektorat Kabupaten/Kota in the province of Aceh. While the task complexity and time pressure does not effect the performance of auditor in Inspektorat Kabupaten/Kota in the province of Aceh.KEYWORDS : motivation, discussion of audit review, task complexity, time pressure, and Performance of auditor